Thresholds - Cornelius-Jablonski, Lynn, author; Lundberg, Thomas R., advisor; Coronel, Patricia D., committee member; Williams, Ron G., committee member; Pettigrew, Ruth, committee member (Colorado State University. Libraries, 2006)
“...by recalling... memories we add to our store of dreams; we are never real historians, but always near poets, and our emotion is perhaps nothing but an expression of a poetry that was lost.” by Gaston Bachelard - Crossing a threshold, embarking on a journey, entering an unknown place. These endeavors can be internal as well as physical. Our world is becoming more and more mapped out: we can carry portable Global Positioning Systems on a voyage at sea and know what longitude and latitude we are occupying at any given moment. Radar systems used in air and ocean transportation identify obstacles. We have phones that connect us to others at the touch of a button. We are relentless in our quest to banish the possibility of being lost or alone in the world. Regardless of our efforts, however, it is still possible to experience the mystery in the unknown. In our physical environment, we can sense this vastness staring into the night sky, out to the unbroken horizon of the sea, or into a dense veil of fog. Our psyches present an even more complex landscape of the unknown. Our dreams, moments of silence, moments of loneliness offer windows into this mystery. Weaving is a way for me to express this internal landscape. As I weave I attempt to create a sort of psychic map to navigate the awe I experience when standing at the edge of infinity, whether it is on a ship's bow, completely out of sight of land, or upon waking from a dream in which another drama unfolds in the vast wilderness of the mind. I am curious about thresholds, the place where a known physical space merges with imagined places, and how these intersections can be embodied in objects. Often we are transported into a dream-like experience through memory. The wedding photograph that evokes a specific time, place, emotional state, for example, or perhaps a tactile memory triggered by a blanket from childhood. However, an object that evokes the unknown is more elusive. Seeing medieval illuminated manuscripts for the first time transported me into a dreamy imaginative state that never existed in my own memory. Despite the lack of firsthand experience, it suggests a cultural memory that is linked to a spiritual searching via the language and lush imagery within the pages of such texts. A roomful of books transports me into a place of wonder, awed by the seemingly infinite potential of human experience. I may not know the stories or the people inhabiting them, but it is the possibility they embody that intrigues me; it is as if I am about to embark on a journey to a place I've never been. This quality of possibility is captured within an ordinary object. This sense of mystery and possibility is why I weave. Tapestry is a medium in which the structure of warp and weft create a longitude and latitude for internal maps I want to use to explore these mysterious states. The process of weaving is a physical and psychic navigation of materials that evolves with the formal "terrain" of shifting colors. The hachure technique allows me to weave jagged shapes that are at once about the surface material and what could be the threshold into another reality. The idea of the voyage or journey is both subject matter and process for me. Weaving tapestries is a physical unfolding of time; I'm never quite sure where the tapestry will take me. While there are plans and formal decisions to be made, an improvisational spirit of exploration is important in the exploration of a threshold and the places just beyond.
Keywords: Tapestry